2002
DOI: 10.1200/jco.2002.08.549
|View full text |Cite
|
Sign up to set email alerts
|

Anxiety Disorders in Cancer Patients: Their Nature, Associations, and Relation to Quality of Life

Abstract: Anxiety symptoms are common in cancer patients. Screening by questionnaire seems to assess anxiety symptoms adequately but discriminates abnormal anxiety inadequately. To improve this, we may need to use criteria such as disruption from anxiety, as illustrated by the impact of anxiety disorders on QOL. There seem to be few oncologic variables that could target screening for anxiety disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
264
1
22

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 407 publications
(303 citation statements)
references
References 39 publications
16
264
1
22
Order By: Relevance
“…Still, the fact that only 17% of visits in our study contained a direct expression of distress is concerning, given the high rates of reported distress in cancer patients [13,24,27,53,54,60]. Patients may not discuss emotional issues because they do not feel it is their oncologists' role to address them [48].…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…Still, the fact that only 17% of visits in our study contained a direct expression of distress is concerning, given the high rates of reported distress in cancer patients [13,24,27,53,54,60]. Patients may not discuss emotional issues because they do not feel it is their oncologists' role to address them [48].…”
Section: Discussionmentioning
confidence: 83%
“…Psychological distress, particularly in the form of anxiety and depression, is common in cancer patients, with a reported prevalence between 30 and 50% [13,24,27,53,54,60]. Psychological distress has been correlated with lower quality of life [3,4,54,58], a desire to hasten death [5], and caregiver distress [30,50,57], as well as increased health-care utilization [15,22,33] and shorter survival [19,35,52].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chronically ill patients suffering from anxiety disorders the optimal mean sum score in the STAI state scale has been identified to be between 44 and 51, and 53 in patients suffering from mood disorders (Kaneda and Fujii 2000;Stanley et al, 2001;Stark et al, 2002). The STAI state has been shown to be satisfactory as a screening instrument to predict anxiety disorders in adolescents (Hishinuma et al, 2001), but it is unclear whether it is a good screening instrument in older people (Patterson et al, 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Mental illnesses were associated with a greater need for information in almost all areas, which corresponds to the study by Park et al [15] that concluded that greater information requirements could be determined in patients suffering from depression. Furthermore, worry and anxiety disorders that frequently arise in cancer patients [34] led to the greatest information requirements. Anxiety regarding the consequences of treatment, which are associated with restrictions in everyday life, were described by Mehnert et al [35] and would be able to explain the information requirements patients with renal diseases and "Other illnesses" have in terms of everyday issues.…”
mentioning
confidence: 99%